IMPACT OF LAND BORDER CLOSURE ON PERFORMANCE OF MANUFACTURING FIRMS IN NIGERIA - Masud, Abdullahi; Aliyu, Usman Baba; Yusuf, Abdullahi Babandako; Ndagi, Salihu; Yusuf, Mohammed Abdullahi; Shu’uibu, Bawa .A (Kashere Journal of Management Sciences, 2024)
The study examined the effect of the land border closure on the economic performance, using the manufacturering industry as a focal lens. The main objective is to expose the level of impact the border closure have left on Nigeria's manufacturing firm performance and the economy as a whole. The Border closure was analysed based on its elements ban on informal cross-border trade, Protectionism, and restriction on sub-regional integration. A comprehensive survey questionnaire was used to collect data from a total of 100 top management staff of 12 manufacturing companies found within the Suleja Abuja axis. Statistic Package for Social Sciences (SPSS) version 22 was used to analyse data by running among other reliability tests, ANOVA, and Regression analysis. The results of the study indicated that ban on informal cross-border trade, Protectionism, and restriction on sub-regional integration all have a significant level of impact on performance level of all the manufacturing companies reviewed. It is therefore concluded in line with Omodunbi et al (2022) that, though the border closure had certain consequences which negate Nigeria’s international trade treaties and commitments, created opportunities that assisted local industries to thrive, thereby leading to increase in the production of locally-made goods which aided the growth and development of the Nigerian Economy. This is however, not to negate the fact that the economy has to grapple with unprecedented level of inflation as a result of high reliance on foreign and imported products. It is therefore, recommended that the Nigerian government should invest highly on local entrepreneurs and the Agricultural sector as this will encourage foreign and local investments aimed towards the progress of the Nigerian Economy